Crash Culpability and the Role of Driver Blood Alcohol Levels - Kufera, Joseph A. (Association for the Advancement of Automotive Medicine, 2006)
Twenty years ago the American Medical Association reported the relationship between blood alcohol concentration (BAC) and crash causation. This study addresses culpability, age, gender and BAC in a population of drivers injured in motor vehicle crashes. Five years of hospital and crash data were linked, using probabilistic techniques. Trends in culpability were analyzed by BAC category. Given BAC level, the youngest and oldest drivers were more likely to have caused their crash. Women drivers had significantly higher odds of culpability at the highest BAC levels. Seatbelt use was also associated with culpability, perhaps as a marker for risk-taking among drinkers.